2018
DOI: 10.29194/njes21010108
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study the Effect of Tool Geometry on Dimensional Accuracy in Single Point Incremental Forming (SPIF) Process

Abstract: Incremental forming is a flexible sheet metal forming process which performed by utilizes simple tools to locally deform a sheet of metal along a predefined tool path without using of dies. One limitations of single point incremental forming (SPIF) process is the error occur between the CAD design and the product profile. This work presents the single point incremental forming process for produced pyramid geometry and studied the effect of tool geometry, tool diameter, wall angle, and spindle speed on the dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Radu and Cristea (2013) demonstrated that during SPIF of products, a greater feed rate reduces part accuracy and higher tool rpm stimulates part accuracy. Bedan and Habeeb (2018) claimed higher dimensional accuracy in Al 1050 parts at higher spindle speed; similar results were reported by Palumbo and Brandizzi (2012) in SPIF of titanium alloy. Sbayti et al (2020) concluded that the shape errors between the attained geometry and the proposed CAD model are reduced by combining numerical models and optimization methodologies.…”
Section: Introductionsupporting
confidence: 78%
“…Radu and Cristea (2013) demonstrated that during SPIF of products, a greater feed rate reduces part accuracy and higher tool rpm stimulates part accuracy. Bedan and Habeeb (2018) claimed higher dimensional accuracy in Al 1050 parts at higher spindle speed; similar results were reported by Palumbo and Brandizzi (2012) in SPIF of titanium alloy. Sbayti et al (2020) concluded that the shape errors between the attained geometry and the proposed CAD model are reduced by combining numerical models and optimization methodologies.…”
Section: Introductionsupporting
confidence: 78%
“…Experimental verification was carried out using different tool paths and materials in the non-axisymmetric part. Aqeel Sabree Bedan [10] studied the influence of the ball tool, the hemispherical tool, and the fillet tool on the part accuracy of AL 1050 sheet metal by an NC (Numerical Control) vertical milling machine. It was found that the tool head diameter had the most significant effect on the geometric accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…There are many different incremental forming (IF) technologies that have been developed, including SPIF, Two-Point Incremental Forming (TPIF), and Double-Sided Incremental Forming (DSIF) [4]. Comparing with the other ISF types, SPIF is now the most commonly used incremental forming technique [5], as revealed in Figure 1 [6].…”
Section: Introductionmentioning
confidence: 99%